Attacks by Anons: A Content Analysis of Aggressive Posts, Victim Responses, and Bystander Interventions on a Social Media Site. (March 2018) - Young, Rachel; Miles, Stephanie; Alhabash, Saleem
Cyberbullying is an area of great anxiety related to adolescents' use of social media. Although the affordances of social media sites often allow aggressive online content to be stored and searched, the actual content of aggressive posts has not been explored in great detail. The purpose of this content analysis was to examine discursive strategies used in aggressive posts, responses, and bystander comments on a social media site that is both popular among young adolescents and a known online site of cyberbullying behavior. A total of 993 question–answer dyads were analyzed. In this sample, aggressors are almost exclusively anonymous. Posters of aggressive content demean profile owners on the basis of social status, romantic success, emotional instability, perceived physical attractiveness, and age. Most profile owners attracted a comment from at least one supportive bystander. In general, bystander comments either attacked aggressive posters for their cruelty or their cowardice at being anonymous or supported profile owners by affirming their physical attractiveness or social competence. A power differential between aggressor and victim is a key feature that distinguishes bullying from other social conflicts among adolescents. Results show that, in the absence of physical power, online aggressors use discursive strategies to affirm their dominance over their victims. In turn, victims of online aggression, as well as supportive bystanders, use a variety of methods to attempt to resolve the power differential. Our findings have implications for development of digital citizenship and anti-cyberbullying initiatives that promote effective bystander behavior online.